The impact of curbside parking regulation on garage demand. (April 2016) - Gragera, Albert; Albalate, Daniel
Abstract: Parking regulation is seen as a good option to encourage modal shift in order to tackle congestion and pollution in metropolitan areas. Market-clearing curbside pricing is rarely implemented and policy makers have tended to make off-street parking provision their main tool to address excessive curbside demand. Research devoted to garage parking is far less well developed, even though public authorities provide both curbside and garage parking that compete with privately operated facilities. In this paper the impact of garage fare and curbside regulation characteristics (fare and type of dedicated spaces) on garage parking demand are investigated. Aggregate occasional and subscribers parking demand is analyzed by means of two different econometric models estimated using a panel from Barcelona's public parking authority (BSM) that covers 34 garage facilities with yearly data for the period 2006–2012. We find that both demand segments show a negative elasticity to garage fare. Only occasional parkers show a clear substitution effect with a curbside premium (€0.55/h). Our finding suggests that the actual pricing efficiency gap in Barcelona can range between €0.45 and €1.05 due to the mismatch between curbside and garage pricing regimes; for which we propose some policy alternatives. This stresses the need for a single integrated market approach to parking management, in order to overcome market distortions and achieve efficiency. Additionally, our results show that the characteristics of curbside parking spaces (allowance and time limits) play a role in garage demand determination, yet pricing is much more efficient trigger for behavioral change. Highlights: Occasional parkers and subscribers show a negative elasticity to garage fares. Curbside and garage parking are substitutes (curb premium €0.55/h). The pricing efficiency gap in Barcelona ranges between €0.45 and €1.05/h. The type of space has an impact on demand (different for each segment). Curbside and garage parking should be integrated into a single management approach.